Antifungal Activity of Alkaloid and Flavonoid Extracted from Curcuma longa - Zeena G. Faisal (Journal of Global Pharma Technology, 2019)
The present study investigates the use of agar well diffusion method and the inhibitory effect of Alkloids and flavonoids againist some pathogenic fungi. The statistical analysis of the results showed of the inhibitory effect of Alkaloids extracted from Curcuma longa on the growth of fusarium and penicillium, there are significant differences below the level of probability (P<0.05) between the inhibitory effectiveness of Alkaloids extracted from Curcuma longa of the studied species, compared with the standard antifungal (Itraconazole), Alkaloids extract of the Curcuma longa gave higher inhibition impact compared with the inhibitory effect of antifungal (Itraconazole) at the concentration 98% .The inhibitory percentage showed the effect of Flavonoids extract of Curcuma longa in growth of fusarium and penicillium, that there are significant differences below the level of probability (P<0.05) between the inhibitory effectiveness of the extract Flavonoids and the fungal genera compared with the standard antifungal (Itraconazole),. Showed Flavonoids is less inhibitory effect of inhibitory effect of Itraconazole antifungal at all concentrations of Flavonoids extracts. The inhibitory effect of Flavonoids extract of Curcuma longa at concentration 99% (22, 25,) mm to fungal species (fusarium and penicillium) respectively.